Drug repurposing of natural depsipeptide from Eleftheria terrae isolated via iChip for anti-breast cancer therapy - Fhatonah, Nuriyatul; Rustandi, Tedi; Abdelmohsen, Usama Ramadan; Rasydy, La Ode Akbar; Ma’sum,; Elghanam, Yomna; Pashar, Imran; Nordin,; Mahal, Ahmed; Riski, Akhmad (Frontiers in Pharmacology, 2025)
Graphical AbstractDiagram showing a drug development process using AI. Left panel depicts molecular structures of teixobactin and clovibactin. Middle section illustrates pharmacochemistry, ADMET pharmacokinetics, and pharmacodynamics targeting with clinical trial simulation using AI. Right section covers side effects, prognosis, and diagnosis using multimodal electronic health records.